Impacts of the Use of Chrysophyllum albidum G. Don on Its Vulnerability and Its Conservation in Benin - ALOWANOU-KELE, Blaise; MISSIHOUN, ANTOINE ABEL HOUMÈNOU; AGBO, Ignace Relique; EWEDJE, EBEN-EZER BABA KAYODE; Hounnakpon Yedomonhan, Hounnakpon; AGBANGLA, CLÉMENT (My University, 2023)
Aims / Objectives: Chrysophyllum albidum is a fruit tree of great socio-economic importance in West Africa. In several localities in Benin, despite the species over-exploitation of the species, few data relating to its viability and the conservation of its genetic diversity exist. The objective of this study is to determine the values and forms of uses, of various organs of the species by the populations, in order to identify their impacts on the vulnerability of the species and its sustainable use. Methodology: A semi-structured survey has collected from 877 an (eight hundred and seventyseven) person’s taken at random, ethnobotanical data on the species. The frequencies of use of the different organs, the index vulnerability of the species, as well as the dendrometric parameters were evaluated. In addition, Cramer's V test was used to analyze the influence of sex and socio-cultural groups on the different uses made of the species. Results: It appears that the species is more and more essential, because it is better known and has priority used in human and animal food, the cure of certain bodily and spiritual diseases but also serves as energy wood and lumber. The frequency of use organs varies from 2.28% (flower) to 99.54% (fruits), passing through 25.88% (root), 35.23% (bark), 49.82% (leaves) and 82.78% (wood). Furthermore, the high number of categories of use (NCU = 6), the frequency of use (FUO = 49.25%), the method of collection (picking and cutting), the types of organs used (wood, fruits, bark, leaves, flower and root), the presence or density of trees of the species in the study environment (less abundant), and the stage of development (adult), made it possible to have the value 2.5 as a vulnerability index. Thus, the degree of stress on the different organs of C. albidum makes the species very vulnerable (VI = 2.50) in Benin. Conclusion: These different data reveal the need to design strategies for the sustainable management of the plant genetic resources of this species useful in Benin.
Keywords: Chrysophyllum albidum; anthropogenic activity; sustainable use; traditional uses; vulnerability; Benin.